(untitled) (Cadernos de Sociomuseologia, 2016)
Our focus will be to indicate a possible understanding of what is a contemporary museum. Whether it’s traditional museum, whether a local museum recognized at the heart of Sociomuseology we always find the idea of patrimonialization of theatricality, public presentation of cultural goods, more or less formal educational processes. Wr also find the socialization of heritage references and collective memory, in the context of the territory of certain social groups, that give shape the very logic of museums understood and assumed as storytellers and intervenors. Key words: Sociomuseology; theatricality; collective memory